2023
DOI: 10.1108/pm-05-2022-0034
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the drivers of data science techniques for real estate professionals in the fourth industrial revolution era

Abstract: PurposeThe study aims to develop a model that supports the application of data science techniques for real estate professionals in the fourth industrial revolution (4IR) era. The present 4IR era gave birth to big data sets and is beyond real estate professionals' analysis techniques. This has led to a situation where most real estate professionals rely on their intuition while neglecting a rigorous analysis for real estate investment appraisals. The heavy reliance on their intuition has been responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(203 reference statements)
0
2
0
Order By: Relevance
“…In Indonesia, barriers to using publicly accessible data management systems, such as the use of a Public Asset Management framework in one of their local governments, are the lack of a supporting institutional and legal framework, the number of areas they must manage, and the lack of data, among others [180]. Osunsanmi et al [181] found that a decentralized real estate market and the management of big data sets using data-management systems are among the leading factors that explain the need for the application of data-science techniques by real estate professionals in Africa. Meanwhile, Renigier-Biłozor et al [23] observed reluctance to accept modern automated tools for property valuation from traditional property appraisers, and stressed the importance of such solutions for overall sustainable development.…”
Section: Practical and Managerial Implicationsmentioning
confidence: 99%
“…In Indonesia, barriers to using publicly accessible data management systems, such as the use of a Public Asset Management framework in one of their local governments, are the lack of a supporting institutional and legal framework, the number of areas they must manage, and the lack of data, among others [180]. Osunsanmi et al [181] found that a decentralized real estate market and the management of big data sets using data-management systems are among the leading factors that explain the need for the application of data-science techniques by real estate professionals in Africa. Meanwhile, Renigier-Biłozor et al [23] observed reluctance to accept modern automated tools for property valuation from traditional property appraisers, and stressed the importance of such solutions for overall sustainable development.…”
Section: Practical and Managerial Implicationsmentioning
confidence: 99%
“…The Industry 4.0 (I4.0) revolution in the logistics sector has increased automation and digitalization with a combinational approach of artificial intelligence and human intelligence for decisionmaking (Golovianko et al, 2023). Researchers in recent times have tried to model the I4.0 challenges and barriers mathematically to plan and execute supply chain initiatives for new technological advancements (Osunsanmi et al, 2023;Nakandala et al, 2023). This study aims to investigate and analyze the crucial I4.0 drivers for logistic management, specifically those contributing to LMD operations.…”
Section: Introductionmentioning
confidence: 99%